Ensure an original and safe "fail-to-open" mode in planar and trench power SiC MOSFET devices in extreme short-circuit operation. (September 2018) - Boige, F.; Richardeau, F.; Lefebvre, S.; Blaquière, J.-M.; Guibaud, G.; Bourennane, A.
Abstract: The purpose of this paper is to present a complete experimentation of the two failure modes in competition that can appear during short-circuit (SC) fault operation of single-chip 1, 2 kV SiC MOSFETs from different manufacturers including planar and trench-gate structures, well-known or recent devices. Ruggedness and selective failure modes are identified in relation with the power density dissipated by the chip and the simulated 1D-thermal junction. Finally, the chips of the devices which failed in a "fail-to-open" mode have been studied in order to find the physical reasons of this original and unusual fail-safe mode.